Perspektif hukum agraria terhadap perlindungan para pihak dalam kontrak pembangunan pipa gas bawah tanah - Pangesti, Shinta; Girsang, Fredsly Hendra Sardol; Widyanti, Khairina; Syari, Shinta Kumala (Widya Bhumi, 2026)
The construction of underground gas pipelines across privately owned land may create legal uncertainty, restrict land use, and trigger compensation disputes when it relies solely on right-of-way agreements without clear minimum standards. This study formulates minimum contractual clauses for right-of-way agreements to protect land-right holders within Indonesia’s agrarian-law framework. Using a normative-juridical method with statutory and conceptual approaches, this research examines primary legal materials consisting of the Basic Agrarian Law, the Land Acquisition Law, Government Regulation Number 18 of 2021, Government Regulation Number 19 of 2021, Minister of ATR/BPN Regulation Number 19 of 2021, and Minister of Energy and Mineral Resources Regulation Number 32 of 2021, as well as secondary legal materials in the form of books, journal articles, and references on right-of-way and easement practices. These materials were obtained through library research and document review and analyzed prescriptively. The findings show that minimum clauses should regulate parties’ authority, corridor identification, access scope, land-use restrictions, duration, compensation, liability, restoration, supervision, and dispute resolution. These standards strengthen legal certainty, reduce conflict, and balance private land rights with energy infrastructure needs. Pembangunan pipa gas bawah tanah yang melintasi tanah milik perseorangan dapat menimbulkan ketidakpastian hukum, membatasi pemanfaatan tanah, dan memicu sengketa kompensasi apabila hanya didasarkan pada perjanjian hak lintas tanpa standar minimum yang jelas. Penelitian ini merumuskan klausul minimum kontrak hak lintas untuk melindungi pemegang hak atas tanah dalam kerangka hukum agraria Indonesia. Dengan menggunakan metode yuridis-normatif melalui pendekatan perundang-undangan dan konseptual, penelitian ini mengkaji bahan hukum primer yang terdiri atas Undang-Undang Pokok Agraria, Undang-Undang Pengadaan Tanah, Peraturan Pemerintah Nomor 18 Tahun 2021, Peraturan Pemerintah Nomor 19 Tahun 2021, Peraturan Menteri ATR/BPN Nomor 19 Tahun 2021, dan Peraturan Menteri Energi dan Sumber Daya Mineral Nomor 32 Tahun 2021, serta bahan hukum sekunder berupa buku, artikel jurnal, dan referensi mengenai praktik hak lintas dan easement. Bahan-bahan tersebut diperoleh melalui studi kepustakaan dan penelaahan dokumen, lalu dianalisis secara preskriptif. Hasil penelitian menunjukkan bahwa klausul minimum harus mengatur kewenangan para pihak, identifikasi koridor, ruang lingkup akses, pembatasan penggunaan tanah, jangka waktu, kompensasi, tanggung jawab, pemulihan tanah, pengawasan, dan penyelesaian sengketa. Standar ini memperkuat kepastian hukum, mengurangi konflik, dan menyeimbangkan hak atas tanah dengan kebutuhan infrastruktur energi.